2018
DOI: 10.1186/s12936-018-2471-6
|View full text |Cite
|
Sign up to set email alerts
|

IgG subclass responses to excreted-secreted antigens of Plasmodium falciparum in a low-transmission malaria area of the Peruvian Amazon

Abstract: BackgroundMalaria in Peru is concentrated in the Amazon region, especially in Loreto, and transmission is focused in rural and peri-urban communities. The government has approved a malaria elimination plan with a community approach and seeks to reduce the risk of transmission through preventive interventions, but asymptomatic and low-parasite-density infections are challenges for disease control and elimination. IgG antibodies play a critical role in combating infection through their ability to reduce parasita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
4
5
0
Order By: Relevance
“…Consistent with previous studies, we showed that total IgG increased with age ( 10 ), that it substantially declined when exposure decreased, that IgG1 and IgG3 were the dominant subclasses, and that there was antigen specific bias of dominance to these subclasses ( 20 , 21 , 25 ). In addition to previous findings, we showed that the decrease in total IgG was consistently driven by the decrease in IgG3 and occasionally by a decrease in IgG1.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies, we showed that total IgG increased with age ( 10 ), that it substantially declined when exposure decreased, that IgG1 and IgG3 were the dominant subclasses, and that there was antigen specific bias of dominance to these subclasses ( 20 , 21 , 25 ). In addition to previous findings, we showed that the decrease in total IgG was consistently driven by the decrease in IgG3 and occasionally by a decrease in IgG1.…”
Section: Discussionsupporting
confidence: 91%
“…Antibody responses to malaria are predominantly cytophilic (IgG1 and IgG3) and have been shown to mediate effector mechanisms that inhibit of parasite growth (19,20), promote opsonic phagocytosis (21) and complement fixation (22,23). Epidemiological studies have demonstrated associations between IgG1 and IgG3 targeting various P. falciparum antigens and different manifestations of immunity, including reductions in the risk of infection, parasite density, clinical disease, and disease severity (15,20,24,25). In general, these associations were stronger for IgG3 compared to IgG1 (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous studies, we showed that total IgG increased with age (46), that it substantially declined when exposure decreased, that IgG1 and IgG3 were the dominant subclasses, and that there was antigen specific bias of dominance to these subclasses (20,21,25). In addition to previous findings, we showed that the decrease in total IgG was consistently driven by the decrease in IgG3 and occasionally by a decrease in IgG1.…”
Section: Discussionsupporting
confidence: 91%
“…Antibody responses to malaria are predominantly cytophilic (IgG1 and IgG3) and have been shown to mediate effector mechanisms that inhibit of parasite growth (19,20), promote opsonic phagocytosis (21) ) and complement fixation (22,23). Epidemiological studies have demonstrated associations between IgG1 and IgG3 targeting various P. falciparum antigens and different manifestations of immunity, including reductions in the risk of infection, parasite density, clinical disease, and disease severity (15,20,24,25). In general, these associations were stronger for IgG3 compared to IgG1 (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…We evaluated whether the natural antibody response to Pvs230D1M in humans would be characterized by higher levels of complement-fixing IgG subclasses. In our analyses of Pv230D1M IgG subclass frequency, IgG1 and IgG3 were shown to be the predominant subclasses during malaria infection and these isotypes are known to fix complement (2933). This suggests that the functional activity of naturally acquired anti-Pvs230 antibody might be enhanced by complement, but this requires further investigation.…”
Section: Discussionmentioning
confidence: 73%